2015
DOI: 10.5539/mas.v9n8p399
|View full text |Cite
|
Sign up to set email alerts
|

Local Community and Tourism Development: A Study of Rural Mountainous Destinations

Abstract: Malaysia is internationally regarded as a popular rural destination because of its natural heritage. Rural tourism is increasingly viewed as a panacea for increasing the economic viability of marginalized areas, stimulating social regeneration, and improving the living conditions of rural communities. This study explores local community involvement in a rural tourism development in Kinabalu National Park, Sabah. We explore how the local community perceives their involvement in a local rural tourism development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…Moreover, based on the results of regression analysis about predicting the effect of empowerment of local stakeholders of tourism on sustainability and development of rural settlements in tourism destinations within marginal areas under study, the effectiveness of indicators such as training and awareness-raising, trust and confidence, access to finance and credits, institutionalization, and cooperation in promoting rural development in study area was demonstrated. Thus, the present findings were consistent with the results of studies in: South Africa, Giampoccolli and Kalis Haywood [7]; West Africa, Manu and Kuuder [31]; Kenya in East Africa, Obonyo and Fwaya [32]; Central America, Matarrita-Cascante et al [32]; South America McCool and Bosak [34]; East and South Asia; Slathia et al [36]; Jaafar et al [37]; and Eastern Europe; Strzelecki [6]. It should be noted that some affecting factors such as knowledge, skills and human resource development, competence, meaning, self-determination, impact and effectiveness have failed to explain development and sustainability of rural settlements in the region.…”
Section: Conclusion and Recommendationssupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, based on the results of regression analysis about predicting the effect of empowerment of local stakeholders of tourism on sustainability and development of rural settlements in tourism destinations within marginal areas under study, the effectiveness of indicators such as training and awareness-raising, trust and confidence, access to finance and credits, institutionalization, and cooperation in promoting rural development in study area was demonstrated. Thus, the present findings were consistent with the results of studies in: South Africa, Giampoccolli and Kalis Haywood [7]; West Africa, Manu and Kuuder [31]; Kenya in East Africa, Obonyo and Fwaya [32]; Central America, Matarrita-Cascante et al [32]; South America McCool and Bosak [34]; East and South Asia; Slathia et al [36]; Jaafar et al [37]; and Eastern Europe; Strzelecki [6]. It should be noted that some affecting factors such as knowledge, skills and human resource development, competence, meaning, self-determination, impact and effectiveness have failed to explain development and sustainability of rural settlements in the region.…”
Section: Conclusion and Recommendationssupporting
confidence: 82%
“…"In some south Asian countries such as India, cooperative groups have played a pivotal role in participation of stakeholders in tourism development" [36]. "In the Southeast Asia (Malaysia), there has been an emphasis on state support to grant loans for investments in areas such as tourism services and products" [37]. "In Eastern Asia, (China) government policies have been concentrated on investing in social capital and involvement of local stakeholders to improve the quality of life and sustainability in China's rural settlements" [38].…”
Section: Introductionmentioning
confidence: 99%
“…Rural tourism benefits local communities through stimulating economic growth, valuing cultural heritage and raising their standard of living. These again encourage positive attitudes and behaviors of communities towards rural tourism development (15,20). Rural community-based tourism can benefit greatly from a targeted and integrated rural development program (21,22).…”
Section: Significance Of Rural Tourismmentioning
confidence: 99%
“…It is also being seen as an alternative for mass tourism (Guerrero, Valdez Pérez, & Ibarra, 2013;Ghaderi, 2004;Sharpley, 2000). Wilson (2001) argued that development of rural tourism is easier in comparison to other development strategies and it has lower costs as well (Jaafar, Bakri, & Rasoolimanesh, 2015). Encouraging rural tourism is a policy which is used not only in developed countries but in developing countries (Iorio & Corsale, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%